Bone marrow mesenchymal stem cells’ osteogenic potential: superiority or non-superiority to other sources of mesenchymal stem cells? - Gholami Farashah, Mohammad Sadegh; Mohammadi, Amirhossein; Javadi, Maryam; Soleimani Rad, Jafar; Shakouri, Seyed Kazem; Meshgi, Shahla; Roshangar, Leila (Cell and tissue banking, 2023)
Skeletal problems are an increasing issue due to the increase in the global aging population. Different statistics reports show that today, the global population is aging that results in skeletal problems, increased health system costs, and even higher mortality associated with skeletal problems. Common treatments such as surgery and bone grafts are not always effective and in some cases, they can even cause secondary problems such as infections or improper repair. Cell therapy is a method that can be utilized along with common treatments independently. Mesenchymal stem cells (MSCs) are a very important and efficient source in terms of different diseases, especially bone problems. These cells are present in different tissues such as bone marrow, adipose tissue, umbilical cord, placenta, dental pulp, peripheral blood, amniotic fluid and others. Among the types of MSCs, bone marrow mesenchymal stem cells (BMMSCs) are the most widely used source of these cells, which have appeared to be very effective and promising in terms of skeletal diseases, especially compared to the other sources of MSCs. This study focuses on the specific potential and content of BMMSCs from which the specific capacity of these cells originates, and compares their osteogenic potential with other types of MSCs, and also the future directions in the application of BMMSCs as a source for cell therapy.